Transgenerational effects of maternal bisphenol: a exposure on offspring metabolic health. (26th October 2018) - Bansal, A.; Li, C.; Xin, F.; Duemler, A.; Li, W.; Rashid, C.; Bartolomei, M. S.; Simmons, R. A.
Abstract: Exposure to the endocrine disruptor bisphenol A (BPA) is ubiquitous and associated with health abnormalities that persist in subsequent generations. However, transgenerational effects of BPA on metabolic health are not widely studied. In a maternal C57BL/6J mice (F0) exposure model using BPA doses that are relevant to human exposure levels (10 μg/kg/day, LowerB; 10 mg/kg/day, UpperB), we showed male- and dose-specific effects on pancreatic islets of the first (F1) and second generation (F2) offspring relative to controls (7% corn oil diet; control). In this study, we determined the transgenerational effects (F3) of BPA on metabolic health and pancreatic islets in our model. Adult F3 LowerB and UpperB male offspring had increased body weight relative to Controls, however glucose tolerance was similar in the three groups. F3 LowerB, but not UpperB, males had reduced β-cell mass and smaller islets which was associated with increased glucose-stimulated insulin secretion. Similar to F1 and F2 BPA male offspring, staining for markers of T-cells and macrophages (CD3 and F4/80) was increased in pancreas of F3 LowerB and UpperB male offspring, which was associated with changes in cytokine levels. In contrast to F3 BPA males, LowerB and UpperB female offspring had comparable body weight, glucose tolerance and insulin secretion as Controls. Thus, maternal BPA exposure resulted in fewer metabolic defects in F3 than F1 and F2 offspring, and these were sex- and dose-specific.